NAHDLATUL ULAMA (NU) DAN PEMAHAMAN KEILMUAN ISLAM AHLUSSUNNAH WAL JAMAAH (ASWAJA) - Firman Amir (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
This article discusses the historicity of Nahdlatul Ulama (NU) and the significant role of Nahdlatul Ulama (NU) in maintaining religious understanding based on the teachings of Ahlussunnah wal Jama'ah in Indonesia. Since its founding in 1926, NU has consistently upheld inclusive, moderate, and tolerant religious values. Using literature review and a qualitative approach, this article analyzes various relevant sources. NU's contribution to practicing the Islamic understanding of Ahlussunnah wal Jama'ah is highly visible in society. Religious values ​​of compassion, courtesy, and knowledge are highly encouraged in preaching. Important figures in the history of NU's founding and the practice of Ahlussunnah wal Jama'ah teachings have also played active roles, such as KH. Hasyim Asy'ari, KH. Abdul Wahab Chasbullah, and KH. Bisri Syamsuri. Nahdlatul Ulama's role in maintaining the understanding of Islam according to Ahlussunnah wal Jama'ah extends beyond increasing intellectual awareness of religion to developing moderate morals, ethics, and Islamic values. Through its understanding of Ahlussunnah wal Jama'ah, NU is producing an intelligent generation with noble morals and capable of making positive contributions to Indonesian society. This summary emphasizes NU's crucial role and contribution to the practice of Ahlussunnah wal Jama'ah in Indonesia. Keywords Nahdlatul Ulama, Historicity, Ahlussunnah wal Jama'ah